Effect of “Om” Chanting on Depression Among College Students - A Pilot Study - Kumar P, Naresh; Srimathi, VS; Sundaran, Jincy (International Research Journal of Ayurveda & Yoga, 2024)
Background: Depression in the early life stage can lead to negative consequences in adult life, which necessitates targeting the young adult population to facilitate prevention. The objective of this study is to assess the effect of “Om” chanting 108 times per day for 3 weeks on depression in freshly inducted first-year Yoga and Naturopathy naïve medical college students. Methods: One-Group Pretest-Posttest Design in which a pretest measure is done followed by a treatment and a posttest for a single group. The intervention of chanting “OM” 108 times per day for 21 days was practiced by the 92 newly joined medical students. An 18-item self-administered Goldberg depression scale was used as the assessment tool for measuring the severity of the depression pre and post-intervention. Results: The average age of the participants was (18.21 ±0.47 years) among which 73.9% had depression ranging from possibly minor depression to severe depression. There was a significant difference in the scores before intervention (M=24.23, SD=13.25) and after intervention (M=15.42, SD=11.96) of OM chanting; t (67)= 6.93, p=0.001 showing chanting of “OM” had a significant reduction on Depression scores among medical students. Conclusion: The study showed that chanting OM 108 times for 21 days has a significant impact on Depression scores among medical students. Om chanting can be a cost-effective intervention and might prevent depression in students. The findings warrant further large-scale studies for strengthening the findings.